2006
DOI: 10.1055/s-2006-932453
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Biosynthetic Pathway Leading to the Complex Nonadride Phomoidride B

Abstract: In this Account we recall our studies into the biosynthesis of the complex fungal secondary metabolite phomoidride B (also known as 114). Our labeling studies revealed this natural product is produced by a remarkable dimerization of a sixteen-carbon anhydride. This unique biosynthetic pathway provides new opportunities in the area of combinatorial biosynthesis for the production of structurally novel unnatural products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…100 Cordyanhydrides A and B (20) from C. pseudomilitaris 101 are novel maleic anhydrides that are the linear dimers or trimers, respectively, of formal C 9 anhydride units, analogous to the cyclic nonadrides. 102,103 We propose that the anhydride forms by the intermolecular aldol condensation of a short chain (C 6 ) unsaturated fatty acid from polyketide or fatty acid biosynthesis with oxaloacetate, or more likely a-ketoglutarate, based on the precedent of the biosynthesis of the dialkylmaleic anhydride in the Streptomyces metabolites tautomycetin 55 and tautomycin. 104 2.2 Nonribosomal peptides 2.2.1 Nonribosomal peptide biosynthesis.…”
Section: Nonreduced Polyketidesmentioning
confidence: 99%
“…100 Cordyanhydrides A and B (20) from C. pseudomilitaris 101 are novel maleic anhydrides that are the linear dimers or trimers, respectively, of formal C 9 anhydride units, analogous to the cyclic nonadrides. 102,103 We propose that the anhydride forms by the intermolecular aldol condensation of a short chain (C 6 ) unsaturated fatty acid from polyketide or fatty acid biosynthesis with oxaloacetate, or more likely a-ketoglutarate, based on the precedent of the biosynthesis of the dialkylmaleic anhydride in the Streptomyces metabolites tautomycetin 55 and tautomycin. 104 2.2 Nonribosomal peptides 2.2.1 Nonribosomal peptide biosynthesis.…”
Section: Nonreduced Polyketidesmentioning
confidence: 99%
“…A previous report showed that the production of 2 was induced under low pH conditions . Therefore, we initially examined the expression of proposed phi genes under both nonproducing and producing conditions.…”
mentioning
confidence: 99%
“…18,19 More recent work has focussed on genome sequencing, knock out experiments and heterologous expression combined with isolation of intermediates leading to further insights into the biosynthesis of nonadrides. [20][21][22][23][24][25] Using heterologous expression in Aspergillus oryzae we have shown that the precursors for cyclisation are formed by an iterative highly reducing polyketide synthase supported by a hydrolase together with citrate-processing enzymes (Scheme 1). Carboxylic acids such as 9 have been shown to undergo spontaneous decarboxylation, yielding 11, and both isomers 10 and 11 may be formed in this fashion.…”
Section: Figure 1 Examples Of Nonadridesmentioning
confidence: 99%